KAIDAH ILMU TAFSIR AL-QUR'AN PRAKTIS DALAM PENGEMBANGAN AL-QUR'AN - Triastuty, Nabila; Nasution, Rolan (MAHABBAH : Jurnal Ilmu Ushuluddin Dan Pemikiran Islam, 2025)
The practical principles of Al-Qur’an interpretation and their relevance in the development of Al-Qur’an as a guide to life for modern society. Practical rules of interpretation play an important role in helping muslims understand and apply the teachings of the Qur’an according to the needs of the times. By priotizing linguistic approaches, contextualization of verses, and relevance to scientific developments, practical rules of interpretation attempt to bridge the gap between classical understanding and application in contemporary life. This article also describes several example of implementation, such as the development of an Islamic education curriculum and social polices based on Al-Qur’an values. The result of the study show that a practical approach in interpreting the Al-Qur’an makes it easy for muslims to connect the spiritual values of the Al-Qur’an with the demands of daily life without losing the essence and depth of the teachings.